Molecular dynamics simulation of oxygen transport characteristics in the electrolyte membrane of PEMFC. Issue 2 (5th February 2018) - Kato, Mahiro; Henry, Asegun; Graham, Samuel; Doan, Duc Hong; Fushinobu, Kazuyoshi
Abstract : Purpose: This paper aims to investigate the oxygen transport characteristics in the electrolyte membrane of proton exchange membrane fuel cell (PEMFC), in particular, the water content dependence and the microscopic view of the molecular transport. Design/methodology/approach: Molecular dynamics simulation is used to examine the oxygen transport characteristics in the electrolyte membrane of PEMFC that we have experimentally observed in our previous study. Findings: Molecular dynamics simulation well predicts the diffusion coefficient of oxygen in the membrane. It was found that the oxygen molecules have preference in their transport passage that governs the property. Originality/value: First attempt is to theoretically examine the experimentally observed water uptake dependence of the oxygen diffusion coefficient in membrane and to explain the mechanism.